How Does AI Support Emergency Medical Services? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Meta Description: Explore how Artificial Intelligence (AI) is revolutionizing Emergency Medical Services (EMS), from AI-powered dispatch and triage to enhanc...
Keywords: AI in Emergency Medicine; Support; Emergency; Medical; Artificial Intelligence; Deep Learning; Healthcare